A rare case of translocation (12;22) (p13;Q) in Ewing′s sarcoma - S K Kousar Jahan; Mangala Gowri Mayanna; B L Kavitha; Akkamahadevi Patil; Prasanna Kumari (Indian Journal of Medical and Paediatric Oncology)
Cytogenetic or immunohistochemical studies are often required to differentiate Ewing′s sarcoma (ES) from other small round cell tumors. Herein we report a case of 13-year-old boy who presented with a large presacral lesion. Hemogram and biochemical parameters were normal except lactate dehydrogenase showing value of 96.40/IU/L, magnetic resonance imaging of the spine showed a large mass in presacral lesion (8 cm × 7 cm × 9 cm), with destruction of the sacrum (S2 S3 and S4) with interspinal extension. Bone scan showed multiple pelvic bone lesions, radiograph of chest, ultrasound of abdomen, pelvis and electrocardiogram were within normal limits. Bone marrow was not involved. Cells from the fine needle aspirate were cultured for short term using RPMI medium and karyotype obtained showed a t(12;22)(p12;q12) instead of the classic t(11;22). Diagnosis of ES was also confirmed by studies using immunohistochemistry for MIC2 which was positive, synaptophysin was inconclusive and leukocyte common antigen, desmin negative. This case provides evidence of the importance of chromosome 22, in the etiology of the disease.